(untitled) (Journal of EAHIL, 2020)
The role of libraries in achieving the UN’s Sustainable Development Goals (SDGs) has become an increasingly important topic in the last years. The authors of this paper talked to Petra Hauke, convenor of the “Environment, Sustainability and Libraries Special Interest Group” (ENSULIB) at the International Federation of Library Associations and Institutions (IFLA) about her work and the ways medical libraries might contribute to implementing the SDGs.